PENGARUH MANAJEMEN MODAL KERJA, LIKUIDITAS, SOLVABILITAS DAN PRODUKTIVITAS TENAGA KERJA TERHADAP PROFITABILITAS: Studi Pada Perusahaan Sub Sektor Pariwisata, Hotel, dan Restoran Yang Terdaftar di BEI Periode 2014-2017 - Dinda Permata Citra Yunanto, - (2019)
This research is a quantitative research that aims to determine between working capital management, liquidity, solvability and labor productivity on profitability in tourism, hotel, and restaurant sector recorded in Indonesian Stock Exchange (IDX). Dependent variable in this research is profitability using Return on Asset (ROA) as a measurement. While the independent variable are working capital management with Cash Conversion Cycle (CCC) as a measurement, liquidity with Current Ratio (CR) as a measurement, solvability with Debt to Equity Ratio (DER) as a measurement and labor productivity with sales to total labor as a measurement. Purposive sampling is used to determine the samples in population of all firm in tourism, hotel, and restaurant sector. The samples used in this study include 21 firms within 4 years (2014-2017). Method of Analysis used is multiple regression method using SPSS V23. The result shows that there are negative significant relation between working management capital, liquidity and solvability on profitability. And labor productivity has no significant positive on profitability.